2016
DOI: 10.1002/2016gl068665
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation of NaCl solution from porous media with mixed wettability

Abstract: Evaporation of saline water from porous media is ubiquitous in many processes including soil salinization, crop production, and CO2 sequestration in deep saline acquirer. It is controlled by the transport properties of porous media, atmospheric conditions, and properties of the evaporating saline solution. In the present study, the effects of mixed wettability conditions on the general dynamics of water evaporation from porous media saturated with NaCl solution were investigated. To do so, we conducted a compr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…This explains why the measured rates in the early stages of the evaporation process from the sand columns saturated with 0.5, 1.0, 1.5, and 2.5 M are almost the same (because in all cases crust forms at the surface that controls the drying process). This conclusion is in line with the results presented recently by Bergstad and Shokri [2016]. They showed that the evaporative mass losses from porous media saturated with salty solutions with varying wettability conditions were nearly the same regardless of the wettability condition due to the effect of the presence of precipitated salt at the surface.…”
Section: Effects Of the Precipitated Salt At The Surface On The Evaposupporting
confidence: 93%
See 1 more Smart Citation
“…This explains why the measured rates in the early stages of the evaporation process from the sand columns saturated with 0.5, 1.0, 1.5, and 2.5 M are almost the same (because in all cases crust forms at the surface that controls the drying process). This conclusion is in line with the results presented recently by Bergstad and Shokri [2016]. They showed that the evaporative mass losses from porous media saturated with salty solutions with varying wettability conditions were nearly the same regardless of the wettability condition due to the effect of the presence of precipitated salt at the surface.…”
Section: Effects Of the Precipitated Salt At The Surface On The Evaposupporting
confidence: 93%
“…Evaporation of saline water from porous media is important in many environmental, engineering, and hydrological processes including vegetation and plant growth, soil salinization, land-atmosphere interaction, functioning of the ecosystem, and crop production [Rodriguez-Navarro and Doehne, 1999;Suweis et al, 2010;Ott et al, 2015;Bergstad and Shokri, 2016]. This has motivated many researchers to investigate various aspects of this process including the effects of grain size, wettability, heterogeneity, and external conditions [Huinink et al, 2002;Guglielmini et al, 2008;Nachshon et al, 2011aNachshon et al, , 2011bEloukabi et al, 2013;Norouzi Rad et al, 2015;Jambhekar et al, 2015;Börnhorst et al, 2016;Dai et al, 2016;Shokri-Kuehni et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…For flows in real systems, such local correlations in material properties can be introduced in many ways. For example, by the roughness typical of a fracture surface [39,40], or by a soil containing grains with a mixture of wettabilities [20,41], or by pore-scale correlations that are present in even relatively uniform sedimentary rock like Berea sandstone [38]. One may expect, therefore, that the types of effects discussed here will apply to just as wide a range of situations.…”
Section: Discussionmentioning
confidence: 99%
“…ambient temperature and relative humidity, wind, solar radiation). This has motivated many researchers to look into the effects of various parameters such as wettability [Sghaier and Prat, 2009;Bergstad and Shokri, 2016], particle size distribution [Eloukabi et al, 2013;Noruzirad et al, 2015], relative humidity [Gupta et al, 2014] and mixture of salt [Jambhekar et al, 2016] on the general dynamics of saline water evaporation from porous media.…”
Section: Introductionmentioning
confidence: 99%